Long Period Ionospheric Disturbances Induced by Atmospheric Pressure Waves From the 2022 Tonga Volcanic Eruption - Dwijendra N. Pandey; Rajesh Rekapalli; J. K. Catherine; V. K. Gahalaut; N. Puviarasan (Earth and Space Science)
Abstract The Tonga‐Hunga volcanic eruption on 15 January 2022 at 04:14:54 UTC produced large perturbations in the lower atmosphere and ionosphere globally. We report that the long period (0.28–16.67 mHz) ionospheric disturbances followed the surface pressure perturbations, which traveled globally. Here, we analyzed the Global Positioning System (GPS) data to understand the propagation of long period ionospheric disturbances together with the pressure waves in the regions along a great circle passing through Tonga, and also in the polar sectors. We also infer the strong westward propagation of ionospheric anomalies from GPS sites in Australia. This response of the ionosphere to the surface pressure fluctuations could be a possible reason for the observed ionospheric perturbations in polar regions. Our results demonstrate that (a) the pressure wave irregularities propagated all over the globe with an average velocity of ∼320 m/s and stimulated the non‐dispersive ionospheric perturbations with the same velocity, (b) the volcano ionospheric disturbances due to multiple eruptions lasted for more than 3 hr and are even noticed in the northern and southern polar regions, (c) the variation of amplitude of the ionospheric perturbations with distance from Tonga follows an exponential decay with some irregularities near the equator, and (d) a low‐frequency surface pressure irregularity of 12 hr duration is observed nearly 36 hr before the main eruption.